Possibilities of Cardiac Scintigraphy with {123}I-Iodophen in Patients with Various Forms of Cardiomyopathies; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Lishmanov Yu. B. Yury Borisovich; Minin S. M. Stanislav Mikhaylovich; Saushkina Y. V.; Gulya M. O. Marina Olegovna (Radiation Technologies in Medicine, 2015)
Title screen